Comprehensive Slope Stability Analysis: Floods and Rapid Drawdown Triggered Road Slope Instability (A Case Study) - Edward Ngii; Anafi Minmahddun; Suyuti Suyuti; Uniadi Mangidi; Fathur Rahman Rustan; Dwiprayogo Wibowo; Muhammad Nurdin (Journal of Engineering and Sustainable Development)
The risks of erosion to road embankments due to increased river water volume, particularly during flood events, often disrupt economic activities such as food and clothing distribution between locations. Therefore, this research investigated the critical impact of rapid drawdown on slope stability for road infrastructure adjacent to the Laeya River in Southeast Sulawesi, Indonesia. To achieve this aim, a comprehensive two-stage method was adopted, and the first included hydrological analysis to simulate flood water levels and predict rapid drawdown scenarios. In the second stage, a detailed geotechnical analysis through finite element method (FEM) was used to assess the stability of the slopes. Consequently, the research findings showed essential safety factor (SF) values under various conditions. The initial SF for the existing condition was 1.20, but after implementing treatment measures, such as slope geometry modification and soil compaction, the value improved to 1.54. However, during flood water level conditions, SF decreased to 1.50 due to the submergence of the slope base. Observation showed that rapid drawdown conditions led to a critical reduction in SF to 1.22, signifying the need for further research on the implications of drawdown. This research provided valuable perceptions and engineering solutions for improving slope stability in river-adjacent road infrastructure.